5n-3=2n+18

Simple and best practice solution for 5n-3=2n+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n-3=2n+18 equation:


Simplifying
5n + -3 = 2n + 18

Reorder the terms:
-3 + 5n = 2n + 18

Reorder the terms:
-3 + 5n = 18 + 2n

Solving
-3 + 5n = 18 + 2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2n' to each side of the equation.
-3 + 5n + -2n = 18 + 2n + -2n

Combine like terms: 5n + -2n = 3n
-3 + 3n = 18 + 2n + -2n

Combine like terms: 2n + -2n = 0
-3 + 3n = 18 + 0
-3 + 3n = 18

Add '3' to each side of the equation.
-3 + 3 + 3n = 18 + 3

Combine like terms: -3 + 3 = 0
0 + 3n = 18 + 3
3n = 18 + 3

Combine like terms: 18 + 3 = 21
3n = 21

Divide each side by '3'.
n = 7

Simplifying
n = 7

See similar equations:

| 5y-7y+1=11 | | 2x+56x+342x-133x= | | 2n+6=16 | | 2x+56x= | | 5r-7r=16 | | 5x-3=x^2-2x+x+6 | | x^2+x-3=0 | | 12m=17 | | (13b-1)-4(3b+3)=-4 | | 6x+5x+3+7=6x+4+4x | | 7*x+9*x=52 | | 35x*4=0 | | 8(b+4)=40 | | 14x-(9x-7)=11+(-3+62) | | (3*x)+5=53 | | 2x(9-7x)=0 | | k*p=16 | | h*h+g*g=64 | | s+5=7 | | s*s-12s+12=0 | | 3+27x+15=5x+18+22x | | 0.75*18+0.25*x=17 | | 0.25x^2-5x=10 | | 4p+2q=28 | | 1+a=b-1 | | 8n-30=42 | | 4p+3q=26 | | (x+-2)(x+-2)=-25 | | 400=16t | | 12x^2+25x-7=0 | | 7m+7n= | | 2x+4x+3y= |

Equations solver categories